Surface effects on the photoconducting properties of SrTiO3 thin films - Bachi, Nicolás (2017)
We report a study of the photoconducting properties of semiconducting SrTiO3 thin films. The photoconducting spectrum shows a pronounced rise around 3.2 eV with a typical indirect gap dependence, involving a transversal optical phonon of 25 meV. While these features remain unaltered under the influence of an applied electric field in ambient conditions, in a vacuum the rest of the spectrum does not, shifting to lower energies for higher electric fields. Time dependent photoconductivity response while illumination is applied confirms the loss of efficiency of the 3.7 eV transition. At low-temperatures, the photoconducting spectrum at low-electric fields has striking similarities to the ones at room-temperature for high-electric fields. This ability to control the photoconducting response through external parameters is explained considering a model of a downward band bending generated by oxygen vacancies at the surface in concomitant with recent findings at the surface of SrTiO3.